Unlocking Premolars with the Pendulum Appliance Approach in Mixed Dentition: A Case Report - Gupta, Sanjana; Dali, Mamta; Koirala, Bandana (Journal of Nepalese Association of Pediatric Dentistry, 2024)
Impaction or ectopic eruption of premolars can also occur due to space loss caused by the early loss of primary molars, often requiring early management. Timely intervention can reduce or eliminate the need for more complex and costly fixed orthodontic treatment, alleviating parental anxiety about future complications and financial burden. The pendulum appliance is an intraoral device used for molar distalization and space regaining with minimum compliance required. This case report explores the utilization of a pendulum appliance for space regaining in a patient with a locked premolar due to premature loss of primary molars resulting in mesial migration of maxillary first permanent molar. The appliance effectively facilitated controlled distalization of the molar, creating sufficient space for the eruption of locked premolar and achieving proper tooth alignment. This improved facial aesthetics, and enhanced self-image, boosting the child’s confidence. Hence, it offers a predictable, efficient, and patient-friendly approach to managing space deficiencies in the mixed dentition phase.